Pulmonary Hypertension in Hemodialysis Patients - Moniruzzaman, M; Islam, MN; Alam, MB; Alam, ABM M; Khan, MMH; Ali, Z; Chowdhury, AW; Chowdhury, MN (Cardiovascular Journal, 2012)
Background: Pulmonary hypertension (PH) has been reported to be high among maintenance dialysis patients. There is a paucity of data on the incidence and prevalence of pulmonary hypertension in chronic kidney disease(CKD) in Bangladeshi patients. Materials and Methods: A total 70 CKD patients (male 47,female 23), who were on conservative management and maintenance hemodialysis were studied for the presence of pulmonary hypertension. The variables studied were hypertension, diabetes, duration of dialysis and the hemoglobin, serum creatinine and serum bicarbonate levels. Results: 68.6% of the patients on maintenance hemodialysis had pulmonary hypertension compared to 8.6% of the prediadysis CKD patients. 97.1% of maintenance dialysis patients had anaemia (Hb <10gm/dl) and 42.9% of patients had metabolic acidosis. Conclusion: The incidence of pulmonary hypertension was highest in the hemodialysis group. Significant Pearsons correlation was found between pulmonary arterial systolic pressure with the duration of hemodialysis, hemoglobin level, serum creatinine, blood sugar and serum bicarbonate level in maintenance hemodialysis patients DOI: http://dx.doi.org/10.3329/cardio.v4i2.10459 Cardiovasc. j. 2012; 4(2): 148-152